2018
DOI: 10.1111/1471-0528.15476
|View full text |Cite
|
Sign up to set email alerts
|

Associations between maternal physical activity in early and late pregnancy and offspring birth size: remote federated individual level meta‐analysis from eight cohort studies

Abstract: In an individual participant meta-analysis, late pregnancy moderate to vigorous physical activity modestly reduced birth size outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 58 publications
4
48
0
1
Order By: Relevance
“…Wu et al 45 used two clinical data sets to develop and test the distributed logistic regression approach. Pastorino et al 46 used distributed regression to examine the association between maternal physical activity and the birth size of the infant using data from eight databases in Europe and the United States. Using the association between antibiotic treatment early in life and the body mass index z score later in life among children in 34 electronic healthcare databases in the United States, Toh et al 47 conducted a proof-of-concept study on how distributed linear regression can be used to examine the benefits and risks of medical products.…”
Section: Distributed Regression Using Summary-level Intermediate Statmentioning
confidence: 99%
“…Wu et al 45 used two clinical data sets to develop and test the distributed logistic regression approach. Pastorino et al 46 used distributed regression to examine the association between maternal physical activity and the birth size of the infant using data from eight databases in Europe and the United States. Using the association between antibiotic treatment early in life and the body mass index z score later in life among children in 34 electronic healthcare databases in the United States, Toh et al 47 conducted a proof-of-concept study on how distributed linear regression can be used to examine the benefits and risks of medical products.…”
Section: Distributed Regression Using Summary-level Intermediate Statmentioning
confidence: 99%
“…Mechanisms of action have been minimally investigated, but are expected to include favourable changes in adiposity, insulin sensitivity, blood pressure, blood lipid and lipoprotein concentrations [7,8]. Children born to active mothers may also benefit from reduced risk of prematurity [9,10], reduced risk of being small-or large-for gestational age [10,11], and a lower fat mass at birth [12].…”
Section: Introductionmentioning
confidence: 99%
“…There is mounting evidence for the specificity of maternal PA during the third trimester and its impact on offspring weight and body composition. Individual meta‐analyses of eight cohort studies recently showed reduced risk of macrosomia and large‐for‐gestational‐age birth associated with moderate to vigorous PA and vigorous PA late in pregnancy but not with early pregnancy PA . Furthermore, these results were not mediated by maternal gestational diabetes and persisted after adjustment of maternal BMI suggesting that PA late in pregnancy may have a direct effect on birth size.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy PA has not been associated with delivery timing; however, there are consistent results showing that maternal PA is associated with reduced risk of large-for-gestational-age birth, without increasing risk of small-for-gestational-age birth (3,4). Furthermore, recent meta-analyses of eight cohort studies indicated that PA in late, but not early, pregnancy was inversely associated with large-for-gestational-age birth (5). Results also showed stronger associations for higher intensity PA, indicating that both timing and intensity of maternal PA may be important for offspring health outcomes.…”
Section: Introductionmentioning
confidence: 95%